Islamic Work Ethics, Organizational Culture, and Employee Performance in a Local Government Human Resource Agency: Evidence from North Musi Rawas, Indonesia - Leni Marlina KS; Rachmiya Saputri; Nur Hamidah (SAFE-Network, 2026)
The performance of local government apparatus needs to be strengthened through human resource management that is not only oriented toward technical competence, but also toward ethical values, work culture, and public service responsibility. This study aims to analyze the influence of the implementation of Islamic work ethics and organizational culture on the performance of BKPSDM employees of North Musi Rawas Regency. This research uses a quantitative approach with an associative design. The research sample consisted of 35 employees selected through saturated sampling. Data were collected using a Likert-scale questionnaire and analyzed using SPSS 27 through validity tests, reliability tests, classical assumption tests, and multiple linear regression analysis. The results show that the implementation of Islamic work ethics, organizational culture, and employee performance are in the very high category. Partially, the implementation of Islamic work ethics has a positive and significant effect on employee performance, while organizational culture has a positive but insignificant effect. Simultaneously, the two variables have a significant effect on employee performance with an R-squared value of 0.505. These findings affirm the importance of maintaining and optimizing the values of trust, responsibility, honesty, discipline, and operational work culture in improving apparatus performance. The implications of this study indicate that strengthening Islamic work ethics needs to be integrated with organizational development, performance evaluation, and the development of a more operational work culture in local government institutions. Its contribution lies in strengthening human resource management based on Islamic values in the local government context.